Radiation detection material, radiation detector, radiation diagnostic system, and method for forming radiation detection material
By employing a protective film that continuously covers the crystal separation region and partially covers the initial layer region of columnar crystal scintillators, the radiation detection material achieves both high spatial resolution and sufficient moisture resistance, overcoming previous technological challenges.
Patent Information
- Application Number
- JP2023176980
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-12
- Publication Date
- 2025-04-24
AI Technical Summary
Existing radiation detectors with columnar crystal scintillators face challenges in achieving both high spatial resolution and sufficient moisture resistance, as protective films either scatter light or fail to provide adequate protection.
A radiation detection material featuring a phosphor with an assembly of columnar crystals, where a protective film continuously covers the entire crystal separation region and partially covers the initial layer region, using a liquid raw material like polysilazane-based silica to maintain moisture resistance and high spatial resolution.
The proposed solution enables a radiation detection material with excellent moisture resistance and high spatial resolution, effectively addressing the limitations of previous technologies.
Smart Images

Figure 2025067205000001_ABST
Abstract
Description
[Technical field]
[0001] RADIATION DETECTION MATERIALS, RADIATION DETECTORS, RADIODIAGNOSTIC SYSTEMS, AND METHODS OF FORMING RADIATION DETECTION MATERIALS FIELD OF THEINVENTION The present invention relates to radiation detection materials, radiation detectors, radiological diagnostic systems, and methods of forming radiation detection materials. [Background technology]
[0002] For example, in the medical field, flat panel detectors (FPDs) used for radiography such as X-rays receive radiation that passes through a subject with a phosphor for detecting radiation (scintillator), and detect the light emitted by the scintillator with a photodetector. In order to efficiently transmit the emitted light to the photodetector, needle-shaped or columnar crystals of an alkali metal halide such as cesium iodide, which are made by deposition, have been used in the crystalline portion of the scintillator.
[0003] Examples of radiation detectors in which a scintillator is formed from a group of columnar crystals include Patent Documents 1 and 2. Patent Document 1 discloses a technique for easily forming a scintillator protective film that covers the scintillator without damaging it and has a peripheral portion that adheres closely to the substrate. Patent Document 2 discloses a technique related to a scintillator plate that can efficiently guide fluorescence by thinning the protective film to prevent deterioration of the scintillator having a columnar structure. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-141190 A [Patent Document 2] JP 2020-041820 A Summary of the Invention [Problem to be solved by the invention]
[0005] Patent Document 1 discloses a case where the gaps between the needle-shaped tip portions of the columnar crystals are filled with a protective film, or where each needle-shaped tip portion is covered with a protective film. However, in these cases, the moisture resistance of the columnar crystals is insufficient, which may lead to a decrease in the spatial resolution of the phosphor. Patent Document 2 discloses a case where each columnar crystal is entirely covered with a protective film. However, in this case, the light emitted and guided by the phosphor is scattered and spreads, which is likely to decrease the spatial resolution of the phosphor.
[0006] The present disclosure has been made in consideration of the above problems, and aims to provide a radiation detection material that is capable of achieving both excellent moisture resistance and high spatial resolution, and a method for forming the same. [Means for solving the problem]
[0007] The radiation detection material of the present disclosure comprises a phosphor having an aggregate of columnar crystals and a protective film formed on the phosphor, the protective film continuously covering the entire crystal separation region of the phosphor and partially covering an initial layer region of the phosphor.
[0008] The method for forming a radiation detection material disclosed herein involves forming a phosphor having an aggregate of columnar crystals, and forming a protective film that continuously covers the entire crystal separation region of the phosphor and partially covers an initial layer region of the phosphor. Effect of the Invention
[0009] According to the present disclosure, a radiation detection material that can achieve both excellent moisture resistance and high spatial resolution is realized. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a vertical cross-sectional view showing the appearance of the radiation detection material according to the present embodiment. [Diagram 2] 3 is a SEM cross-sectional photograph showing the appearance of the radiation detection material according to the present embodiment. [Diagram 3]FIG. 2 is a cross-sectional view showing the appearance of the radiation detection material according to the present embodiment. [Figure 4] FIG. 2 is a schematic diagram showing a regular tetrahedral structure of silica constituting the protective film. [Diagram 5] 1 is a cross-sectional view showing a radiation detector including a radiation detection material according to an embodiment of the present invention. [Figure 6] FIG. 1 is a schematic diagram showing a radiation diagnostic system having a radiation detector equipped with the radiation detection material according to the present embodiment. [Figure 7] FIG. 11 is a characteristic diagram showing the relationship between the number of days elapsed since the creation of the protective film and MTF(2) for Comparative Example 1 and the Example. [Figure 8] FIG. 2 is a schematic diagram showing a state in which a protective film is formed using a spray coater in Comparative Examples 2 and 3 and an Example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. In the following description, components common to multiple drawings are given common reference numerals. Therefore, the common components will be described with mutual reference to multiple drawings, and the description of the components given the common reference numerals will be omitted as appropriate.
[0012] [Composition of radiation detection materials] FIG. 1 is a vertical cross-sectional view showing the state of the radiation detection material according to this embodiment, and (a) and (b) are cut in different ways. Depending on the way the cross-section is cut, the columnar crystals 101 may be spaced apart as shown in FIG. 1(b). FIG. 2 is a cross-sectional photograph taken by SEM showing the state of the radiation detection material according to this embodiment, where (a) shows a cross-section of an initial layer region of the columnar crystal group of the phosphor, and (b) shows a cross-section of a crystal separation region of the columnar crystal group of the phosphor. FIG. 3 is a cross-sectional view showing the state of the radiation detection material according to this embodiment, where (a) shows a cross-section of an initial layer region of the columnar crystal group of the phosphor, and (b) shows a cross-section of a crystal separation region of the columnar crystal group of the phosphor.
[0013] 1(a) and 1(b), the radiation detection material of this embodiment includes a phosphor (scintillator) having a columnar crystal group 110, which is an aggregate of columnar crystals 101, on a substrate 100, and a moisture-resistant protective film 104 formed on the phosphor to protect the phosphor. The protective film 104 is made of, for example, silica (silicon dioxide (SiO2)).
[0014] Each of the columnar crystals 101 constituting the columnar crystal group 110 contains an alkali metal halide, such as cesium iodide. The columnar crystal group 110 of the phosphor is composed of an initial layer region 102 which is a region in the lower part of the columnar crystals 101, and a crystal separation region 103 which is a region in the upper part of the columnar crystals 101. In this embodiment, the protective film 104 continuously covers the entire crystal separation region 103 of the phosphor, and also partially covers the initial layer region 102 of the phosphor.
[0015] The initial layer region 102 of the phosphor refers to a region where fine crystal nuclei are formed on the substrate 100 in the initial stage of film formation in the deposition process of cesium iodide columnar crystals. In the initial layer region 102, the crystal nuclei are formed by selecting the substrate temperature, pressure, and film formation rate. <100> The initial layer region 102 is a region where the thickness of the phosphor is from 10 μm to less than several tens of μm.
[0016] The crystal separation region 103 of the phosphor is formed by further film formation from the initial layer region 102, and the crystal orientation of the columnar crystals 101 changes. <100> This refers to the region where the phosphor is oriented in a fixed direction and grows into a larger columnar crystal. The crystal separation region 103 is a region where the phosphor film thickness is several tens of μm or more. In the columnar crystal group, which is an aggregate of the columnar crystals 101, gaps are formed between each columnar crystal. For example, due to the ratio of the refractive index of cesium iodide (approximately 1.8) to the refractive index of air (1.0), light undergoes repeated total reflection in the high-refractive index cesium iodide columnar crystals, and is effectively guided to the light-receiving element.
[0017] In a group of phosphor columnar crystals, if a protective film is formed so as to embed (fill) the gaps between the columnar crystals, the following problem occurs. The refractive index difference when the gaps between the columnar crystals are filled with a protective film is smaller than the refractive index difference when the gaps are air layers. If the refractive index difference is small, the critical angle at which total reflection occurs at the sidewall of the columnar crystal when the emitted light propagates through the columnar crystal becomes large, and the light guided through the columnar crystal is more likely to dissipate outside the columnar crystal, which may reduce the spatial resolution.
[0018] On the other hand, if there is no protective film on the side walls of the columnar crystals in the columnar crystal group of the phosphor, the phosphor cannot obtain sufficient moisture resistance. Columnar crystals have a high aspect ratio and a very large specific surface area compared to normal planar films. In particular, in the case of columnar crystals of deliquescent alkali metal halides, they easily deliquesce when exposed to water vapor in the atmosphere, causing the columnar crystals to fuse together and impairing the planarity of the side walls. In deliquescent alkali metal halides, the emitted light propagates between the columnar crystals or scatters at the interfaces before reaching the light receiving element, which may reduce the spatial resolution of the radiation detector.
[0019] In this embodiment, specifically, as shown in FIG. 2(a), in the initial layer region 102, the columnar crystals 101 of the phosphor are in contact with each other and connected to each other, and gaps 111 are formed between the columnar crystals 101. In the initial layer region 102, the orientation and size of the columnar crystals 101 are not yet completely determined. In the initial layer region 102 of the phosphor, the columnar crystals 101 of the columnar crystal group 110 are in contact with each other and connected to each other, and the outer shape of each columnar crystal 101 is unclear. In the initial layer region 102, as shown in FIG. 3(a), the protective film 104 is discontinuously formed so as to be exposed at the gaps 111 without filling the gaps 111 formed in the columnar crystal group 110, and partially covers the side surfaces of the columnar crystals 101. In the initial layer region 102, the thickness of the protective film 104 partially present on the side surfaces of the columnar crystals 101 is smaller than the distance between the opposing columnar crystals 101. Here, if the voids 111 in the initial layer region 102 are filled more with the protective film 104, the light emitted by the phosphor and guided therethrough is scattered and spread, which is undesirable since it reduces the spatial resolution. In this embodiment, in the initial layer region 102, the protective film 104 is discontinuously formed so as to be exposed in the voids 111, and by partially covering the side surfaces of the columnar crystals 101, high spatial resolution can be obtained while maintaining moisture resistance. By using a liquid raw material as a film forming material for the protective film 104, in the initial layer region 102, the liquid raw material for the protective film 104 partially permeates the voids 111 in the regions where the outlines of the columnar crystals 101 are unclear, and the protective film 104 is formed discontinuously.
[0020] As shown in FIG. 2(b), in the crystal separation region 103, the size of each columnar crystal 101 becomes large, the columnar crystals 101 are separated from each other, and gaps 111 are formed and maintained between the columnar crystals 101. In this embodiment, in the crystal separation region 103, as shown in FIG. 3(b), the protective film 104 continuously covers the surface of the columnar crystal group 110 so that gaps 111 exist between the columnar crystals 101. In the crystal separation region 103, the thickness of the protective film 104 is set to be equal to or smaller than the distance between the opposing columnar crystals 101. Here, if the protective film 104 is formed in the crystal separation region 103 so as to embed (fill) the gaps 111 between the columnar crystals 101, the light guided in the columnar crystals is likely to dissipate outside the columnar crystals, and the spatial resolution may be reduced. Moreover, if the protective film 104 is formed discontinuously on the columnar crystals 101 in the crystal separation region 103, sufficient moisture resistance of the phosphor cannot be obtained, which is undesirable. By using a liquid raw material as the material for the protective film 104, the liquid raw material permeates the voids 111 in the crystal separation region 103 by capillary action, and a continuous protective film 104 is formed while maintaining the voids 111. As a result, even though the protective film 104 is also formed in the initial layer region 102, sufficient moisture resistance of the phosphor in the crystal separation region 103 is maintained.
[0021] As described above, in this embodiment, the protective film 104 is formed continuously with gaps 111 in the crystal separation region 103 of the phosphor, and is formed discontinuously with gaps 111 in the initial layer region 102 of the phosphor. This realizes a radiation detection material that can achieve both excellent moisture resistance and the high spatial resolution of the phosphor.
[0022] [Protective film] As the liquid raw material for the protective film used in this embodiment, for example, a liquid raw material of silica is used. Specifically, a liquid containing a polysilazane-based inorganic polymer, which is a silica conversion material consisting of silicon, nitrogen, and hydrogen, such as perhydropolysilazane, and having its concentration adjusted with an organic solvent and various catalysts added as appropriate is preferable. Depending on the type of liquid raw material selected, heating may be performed appropriately during the hydrolysis reaction or the conversion reaction to silica glass, but it is preferable to select a liquid raw material in which the reaction occurs at room temperature for convenience. If the concentration of the silica conversion material in the liquid raw material for the protective film is less than 0.5%, the continuity of the protective film formed is insufficient and the moisture resistance becomes insufficient, which is not preferable. Also, if the concentration of the silica conversion material in the liquid raw material for the protective film is greater than 2%, the gaps of the columnar crystals are filled with the protective film formed, or before the liquid raw material is impregnated into the phosphor, the organic solvent dries and the conversion to silica proceeds outside the columnar crystal group of the phosphor. This is not preferable because cracks occur when the applied protective film dries, or the phosphor floats or peels off from the substrate. Generally, it is preferable to set the concentration of the silica conversion material to 0.5% or more and 2% or less, since this makes it possible to achieve both excellent moisture resistance and high spatial resolution of the phosphor.
[0023] [Protective film thickness] As an example of the radiation detection material according to this embodiment and a comparative example of a radiation detection material without a protective film, the content of Si (wt%) in the crystal separation regions (tip and middle) and initial layer region of the phosphor was investigated. Here, the analysis was performed using energy dispersive X-ray fluorescence spectroscopy (EDX). The analysis results are shown in Table 1 below.
[0024] [Table 1]
[0025] As shown in Table 1, in the comparative example having no protective film, almost no Si is present in the crystal separation region and initial layer region of the phosphor. In contrast, in the examples, the presence of Si is confirmed in the crystal separation region and initial layer region of the phosphor on which a protective film is formed. Here, in the examples, the amount of Si is greatest at the tips of the columnar crystals in the crystal separation region, followed by the middle portion, with some Si also present in the initial layer region. From the above, it is seen that in the radiation detection material according to this embodiment, a protective film is formed which becomes thinner in the order of the tips, middle portion, and initial layer region of the crystal separation region.
[0026] Furthermore, the radiation detection material according to this embodiment was observed using a transmission electron microscope (TEM). As a result, it was confirmed that the thickness of the protective film according to this embodiment in the initial layer region is thinner than that in the crystal separation region, that is, the thickness in the crystal separation region is 4 nm or more and 5 nm or less (about 4 nm to 5 nm), and the thickness in the initial layer region is 5 nm or less (about 0 to 5 nm). As shown in FIG. 4, the protective film, which is a silica film, is considered to form a regular tetrahedral structure (height about 0.216 nm) by repeating four oxygen (O) atoms coordinated to silicon (Si) (Si-O bond length is about 0.162 nm). Then, the number of molecular layers in the protective film according to this embodiment, that is, the number of repetitions of the regular tetrahedral structure, can be estimated to be about 16 molecular layers or more and 25 molecular layers or less (about 16 layers to 25 layers) in the crystal separation region and 25 separation layers or less (0 layers to 25 layers) in the initial layer region. It is believed that a protective film having such a thickness provides sufficient moisture resistance for the phosphor.
[0027] [Protective film coverage] The coverage of the protective film in the thickness direction of the phosphor in the radiation detection material according to the embodiment will be described. For example, when forming columnar crystals of a phosphor on a substrate using a film forming method such as a deposition method, the columnar crystals that grow from crystal nuclei of fine diameters gradually undergo selection and fusion to form a group of columnar crystals, so that the columnar diameter of the columnar crystals increases as the film thickness increases. On the other hand, the interval between the columnar crystals is extremely small between fine crystal nuclei, but as the film thickness increases, the separation between the columnar crystals progresses, and from a certain film thickness, the interval is maintained at a roughly constant interval. When the protective film of this embodiment is formed in an initial deposition region consisting of crystal nuclei of fine diameters, the protective film is filled to fill the gaps between the columnar crystals, eliminating the gaps. In this case, the light guided through the phosphor is scattered, and the spatial resolution is reduced.
[0028] The protective film of this embodiment is formed by utilizing the capillary phenomenon of the liquid raw material. Therefore, as shown in FIG. 1(a), the coverage of the protective film gradually changes from a discontinuous coverage state to a continuous coverage state from the initial layer region toward the crystal separation region. In the crystal separation region, the separation between the columnar crystals progresses sufficiently and the gaps can be clearly confirmed. In this case, even if the side walls of the columnar crystals are covered with the protective film in the crystal separation region, the protective film is continuously formed while maintaining the gaps between the columnar crystals. This makes it possible to improve the moisture resistance of the phosphor without impairing the spatial resolution of the phosphor.
[0029] [Protective film formation method] As a method for forming the protective film of this embodiment, a method using a liquid source such as spin coating, spray coating, dip coating, flow coating, bar coating, etc. is appropriately selected. By using such a method, it is possible to easily obtain a coating of a desired thickness on the columnar crystals, compared to, for example, a vapor phase growth method. In addition, by using a liquid source, it is easy to supply a large amount of source material to the columnar crystal group, particularly to the recesses on the columnar crystal surface, so that it is also possible to reduce the surface roughness due to the unevenness of the columnar crystal surface.
[0030] For example, by using the spin coating method, the applied liquid raw material is allowed to remain at the tip of the columnar crystal for a long time due to the centrifugal force caused by the rotation, which is preferable because it makes it easier to form a protective film at the tip of the columnar crystal. In addition, it is also possible to suppress the formation of a protective film between the columnar crystals to the minimum necessary. In addition, by using the spray coating method, the amount of the raw material solution applied to the large-area substrate can be made uniform. In addition, by using the dip coating method, it is possible to supply a large amount of liquid raw material to both sides of the substrate at once. Furthermore, it is also possible to suppress the formation of a protective film between the columnar crystals by holding the tip of the columnar crystal facing vertically downward during application or drying of the liquid raw material. If necessary, it is also possible to promote the chemical reaction by appropriately raising the temperature or heating during raw material supply or application, or even humidifying to an extent that the columnar crystals do not deliquesce, to the extent that the columnar crystals do not deliquesce.
[0031] When a phosphor is formed by deposition, particularly when there is an abnormal crystal growth portion with a larger unevenness than usual, a very thin coating process may be performed before forming the protective film of this embodiment. In this coating process, a very thin coating process is performed on the phosphor by vapor deposition using a metal alkoxide such as a metal alkoxide to form a protective thin film. This coating process is a measure to suppress the deterioration of the phosphor's characteristics during the next process or the period required for storage, that is, to maintain the moisture resistance of the phosphor. The phosphor may be subjected to the coating process, and then a flattening process to reduce the surface roughness due to the unevenness of the phosphor may be performed before forming the protective film of this embodiment. The flattening process may be performed by a method of removing the abnormal crystal growth portion in addition to a method of pressing with a flat plate or roller, and is not limited to any method as long as it can reduce the phosphor surface roughness.
[0032] [Spray coat] In the present embodiment, the protective film is formed by spray coating. In this case, the amount of the liquid material applied to the phosphor surface is controlled by the wet film thickness, so that the protective film of the present embodiment can be easily formed over a large area.
[0033] Wet film thickness is the film thickness immediately after the liquid material is applied, and can be expressed by the following formula, where W is the wet film thickness, G is the amount discharged per unit time, L is the total nozzle movement distance, S is the nozzle scanning speed, d is the liquid material density, and A is the application area. W = [(G × L / S) / d] / A
[0034] For example, if the discharge rate per unit time is 7.2 g / min, the application time is 2 minutes, the density of the liquid material is 0.8 g / cc, and the application area is 30 cm square, the wet film thickness will be 200 μm. The applied liquid material quickly penetrates the phosphor, and in the process of drying the organic solvent, silica conversion occurs and a protective film is formed.
[0035] If the wet film thickness is less than about 75 μm, the liquid raw material supplied to the crystal separation region of the phosphor is reduced, the continuity of the protective film covering the crystal separation region of the phosphor is lost, and the moisture resistance becomes insufficient, which is undesirable. Also, if the wet film thickness is more than about 300 μm, before the liquid raw material is impregnated into the phosphor, the organic solvent dries and the conversion to silica progresses outside the columnar crystal group of the phosphor, which is undesirable because the phosphor floats or peels off from the substrate. Therefore, by forming the wet film thickness to be 75 μm or more and 300 μm or less (about 75 μm to about 300 μm), the protective film can be continuously formed in the crystal separation region without causing the phosphor to float or peel off from the substrate.
[0036] [Phosphor] The base material of the phosphor (scintillator) in the radiation detection material according to this embodiment can be selected from alkali metal halide compounds capable of forming columnar crystal groups, such as cesium iodide and cesium bromide. In order to impart sufficient light-emitting function to the base material, the base material may contain, as an activator, for example, thallium iodide or thallium bromide. The phosphor is formed by a general vacuum film formation method, such as a vapor deposition method.
[0037] [evaluation] The size and change of the column diameter of the phosphor columnar crystals in the prepared radiation detection material are evaluated using, for example, a scanning electron microscope (SEM). The formation state of the protective film is evaluated using, for example, element mapping by energy dispersive X-ray fluorescence spectroscopy (EDX) or a transmission electron microscope (TEM). The spatial resolution characteristics can be quantitatively compared by measuring the modulation transfer function (MTF). The detective quantum efficiency (DQE) is evaluated using various light receiving elements such as a charge coupled device (CCD) or a complementary metal oxide semiconductor (CMOS), and a photodetector such as a camera. The chemical composition of the evaporated film is evaluated using, for example, X-ray fluorescence analysis or inductively coupled plasma analysis, and the crystallinity is evaluated using, for example, X-ray diffraction analysis.
[0038] [Radiation detector] The radiation detecting material according to the present embodiment is applied to a radiation detector. FIG. 5 is a cross-sectional view showing a radiation detector including the radiation detection material according to this embodiment, where (a) shows a direct type radiation detector and (b) shows an indirect type radiation detector.
[0039] As shown in Fig. 5(a), the direct type radiation detector according to this embodiment is configured by forming a radiation detecting material 510 on a sensor substrate 505, and arranging a reflective layer 503 on the radiation detecting material 510 via an adhesive layer 501. The sensor substrate 505 is a substrate on which a large number of optical sensors (pixels) each having a photoelectric conversion element, a switching element, etc. are arranged. The radiation detecting material 510 is formed by forming a protective film covering the phosphor according to this embodiment described above. In Fig. 5(a), the incident direction of radiation is indicated by an arrow 500.
[0040] As shown in Fig. 5(b), the indirect type radiation detector according to this embodiment includes a structure in which a radiation detecting material 510 is formed on a substrate 504 via a reflective layer 503, and a sensor substrate 502 on whose upper surface an adhesive layer 501 is provided. This radiation detector is configured such that the upper surface of the radiation detecting material 510 of the structure faces the adhesive layer 501 on the sensor substrate 502. The sensor substrate 502 is a substrate on which a large number of optical sensors (pixels) each having a photoelectric conversion element, a switching element, etc. are arranged. The radiation detecting material 510 is formed by forming a protective film covering the phosphor according to this embodiment described above. In Fig. 5(b), the incident direction of radiation is indicated by an arrow 500.
[0041] 5(a) and (b), in order to adjust the spatial resolution and sensitivity, optical elements such as a fiber optic plate (FOP) and a light absorbing filter may be added. These optical elements are disposed between the optical sensor substrate 505 or 502 and the radiation detection material 501.
[0042] The above-mentioned radiation detection material and radiation detector can be applied to a radiation detection device (radiography device) that detects radiation. X-rays are typically used as the radiation, but in addition to α-rays, β-rays, γ-rays, etc., which are beams formed of particles (including photons) emitted by radioactive decay, beams having the same or higher energy, such as particle beams and cosmic rays, can also be included.
[0043] According to this radiation detector, more accurate radiation detection is possible by using the radiation detection material 510 that allows both excellent moisture resistance and high spatial resolution to be achieved.
[0044] [Radiation diagnostic system] The radiation imaging apparatus according to this embodiment is applied to a radiation diagnostic system. FIG. 6 is a schematic diagram showing a radiation diagnostic system having a radiation detection device (radiography device) equipped with the radiation detection material according to this embodiment.
[0045] In the radiation diagnostic system according to this embodiment, the radiation detector of this embodiment is used in the radiation detection device 630. In this radiation diagnostic system, radiation 611 generated from a radiation source 610, which is a radiation generation device, passes through a chest 621 of a subject 620, such as a patient, and enters the radiation detection device 630. The radiation 611 that enters the radiation detection device 630 contains information about the inside of the patient 620, and the radiation detection device 630 obtains electrical image information corresponding to the radiation 611. This image information is converted into a digital signal, and then a predetermined arithmetic process is performed by a processor 640, which is, for example, an arithmetic processing device.
[0046] A user such as a doctor can view a radiation image corresponding to this electrical information, for example, on a display 650 in a control room. The user can transfer the radiation image or its data to a remote location by a predetermined communication means 660, and can view this radiation image on a display 651 in a doctor's room, which is another location. The user can also record this radiation image or its data on a predetermined recording medium, for example, on a film 671 by the processor 770.
[0047] Although some suitable examples have been shown above, the present invention is not limited to these, and some of them may be modified without departing from the spirit of the present invention. In addition, the individual terms described in this specification are merely used for the purpose of explaining the present invention, and it goes without saying that the present invention is not limited to the strict meaning of the terms, and may include equivalents thereof.
[0048] According to this radiation diagnostic system, it is possible to perform a more accurate diagnosis by using the radiation imaging device 630 having a radiation detection material that can achieve both excellent moisture resistance and high spatial resolution. EXAMPLES
[0049] Hereinafter, specific examples according to the present embodiment will be described based on comparison with various comparative examples. Fig. 7 is a characteristic diagram showing the relationship between the number of days elapsed since the formation of the protective film and MTF(2) for Comparative Example 1 and the Example. Fig. 8 is a schematic diagram showing the formation of the protective film using a spray coater in Comparative Examples 2 and 3 and the Example.
[0050] [Comparative Example 1] In Comparative Example 1, a vacuum deposition apparatus was used to form a phosphor having a columnar crystal structure using cesium iodide as a base material and thallium iodide as an activator, and then a protective film was formed using ethyl silicate as a material.
[0051] First, a material supply source filled with cesium iodide as a deposition matrix material, a material supply source filled with thallium iodide as a deposition activator material, and a substrate were placed in a vacuum deposition apparatus. The substrate was a glass substrate with an aluminum reflective layer of about 100 nm thick and silicon dioxide layer of about 50 nm thick. After evacuating the inside of the vacuum deposition apparatus to 0.01 Pa or less, current was gradually passed through each material supply source to heat it, and when the set temperature was reached, the substrate was rotated while the shutter installed between the substrate and the material supply source was opened to start film formation. The substrate temperature was gradually raised to 80°C to 160°C. While checking the state of film formation, the shutter was closed when the desired film thickness was formed to end the film formation. After cooling the substrate and material supply source to room temperature, ethyl silicate was quickly brought into contact with the deposition film, which is a phosphor, by vapor phase growth method, and the film was covered with a protective film.
[0052] The deposition surface of the phosphor vapor deposition film was attached to a CMOS photodetector via an FOP, and an image was obtained by irradiating X-rays conforming to the international standard radiation quality RQA5 from the substrate side. In addition, the MTF(2) at a spatial frequency of 2Lp / mm, which is an index of the spatial resolution of the radiation detection material, was determined by an edge method using a tungsten knife edge. The sample was stored in an environment of 25°C and 50% humidity, and MTF measurements were performed every elapsed days. If the MTF(2) value after 5 days is set to 1, a time-dependent change curve was obtained as shown in Comparative Example 1 in FIG. 7. The relative MTF(2) value gradually decreased, reaching 0.76 after 30 days, indicating a decrease in spatial resolution.
[0053] [Comparative Example 2] In Comparative Example 2, a phosphor having a columnar crystal structure was formed using a vacuum deposition apparatus with cesium iodide as a base material and thallium iodide as an activator, and then a protective film was formed using perhydropolysilazane.
[0054] The analytical results for Comparative Example 2, and Comparative Example 3 and Examples described below are shown in Table 2 below.
[0055] [Table 2]
[0056] A phosphor was formed as a deposition film on a substrate having a reflective film, and was covered with ethyl silicate in the same manner as in Comparative Example 1, and was quickly set in the spray coater of FIG. 8. A liquid raw material containing 1% perhydropolysilazane in a dibutyl ether solvent was used to discharge the liquid raw material 804 onto the phosphor 801 formed on the substrate 800. Specifically, the liquid raw material 804 was discharged at a discharge amount of 1.93 g and a scanning speed of 150 mm / sec while scanning the nozzle 802 in the direction of the arrow 803, to form a protective film 805. At this time, the wet film thickness of the protective film 805 was 52 μm. After spray coating, the protective film 805 was dried in an environment with a temperature of 25° C. and a humidity of 50%, and degassing was performed for 30 minutes while evacuating the vacuum vessel to −0.1 MPa on a Bourdon tube pressure gauge. As in Comparative Example 1, the sample was stored in an environment with a temperature of 25°C and a humidity of 50%, and the change in MTF(2) over time was measured at each day that passed. As a result, as shown in Comparative Example 2 in Table 2, if the MTF(2) value after 5 days was taken as 1, it became 0.83 after 30 days, indicating a decrease in spatial resolution.
[0057] [Comparative Example 3] In Comparative Example 3, a phosphor having a columnar crystal structure was formed using a vacuum deposition apparatus with cesium iodide as a base material and thallium iodide as an activator, and then a protective film was formed using perhydropolysilazane.
[0058] A phosphor was formed as a deposition film on a substrate having a reflective film, and the process was carried out in the same manner as in Comparative Example 1 up to the point of coating with ethyl silicate, and the substrate was quickly set in the spray coater of FIG. 8. A liquid raw material containing 5% perhydropolysilazane in a dibutyl ether solvent was used to discharge the liquid raw material 804 onto the phosphor 801 formed on the substrate 800. Specifically, the liquid raw material 804 was discharged at a discharge amount of 6.17 g and a scanning speed of 50 mm / sec while scanning the nozzle 802 in the direction of the arrow 803, to form a protective film 805. At this time, the wet film thickness of the protective film 805 was 400 μm. After spray coating, the protective film 805 was dried in an environment with a temperature of 25° C. and a humidity of 50%, and degassing was carried out for 30 minutes while evacuating the vacuum vessel to a Bourdon tube pressure gauge of −0.1 MPa. As in Comparative Example 1, the samples were stored in an environment with a temperature of 25°C and a humidity of 50%, and the MTF(2) value after five days for Comparative Example 2 was set to 1. When the MTF(2) value after five days for Comparative Example 3 was measured and compared, it was 0.78 as shown in Comparative Example 3 in Table 2, indicating an early decrease in spatial resolution.
[0059] [Example] In this embodiment, a vacuum deposition apparatus was used to form a phosphor having a columnar crystal structure using cesium iodide as a base material and thallium iodide as an activator, and then a protective film was formed using perhydropolysilazane.
[0060] The phosphor was formed as a deposition film on a substrate having a reflective film, and was covered with ethyl silicate in the same manner as in Comparative Example 1, and was quickly set in the spray coater of FIG. 8. A liquid raw material containing 0.5% to 2% perhydropolysilazane in a dibutyl ether solvent, 0.5%, 1%, and 2%, respectively, was used, and this liquid raw material 804 was discharged onto the phosphor 801 formed on the substrate 800. Specifically, the discharge amount and scanning speed were set for each of the liquid raw material 804, and the liquid raw material 804 was discharged while scanning the nozzle 802 in the direction of the arrow 803, to form a protective film 805. At this time, the wet film thickness of each protective film 805 was the value shown in the example of Table 2. After spray coating, the substrate was dried in an environment with a temperature of 25°C and a humidity of 50%, and degassed for 30 minutes while evacuating the substrate in a vacuum container to a Bourdon tube pressure gauge of -0.1 MPa. The change over time in MTF(2) was measured in the same manner as in Comparative Example 1. As a result, if the MTF(2) value after 5 days in Comparative Example 2 is taken as a relative value of 1, then as shown in the examples in FIG. 7 and Table 2, almost no deterioration in spatial resolution was observed in any of the samples after 30 days, and it was found that both excellent moisture resistance and high spatial resolution could be achieved at each wet film thickness.
[0061] The disclosure of the various embodiments includes the following configurations and methods. (Configuration 1) A phosphor having an aggregate of columnar crystals; A protective film formed on the phosphor; It is equipped with The protective film continuously covers the entire crystal separation region of the phosphor, and partially covers the initial layer region of the phosphor. A radiation detection material comprising: (Configuration 2) The thickness of the protective film is equal to or less than the distance between the opposing columnar crystals. 2. The radiation detection material according to claim 1. (Configuration 3) the protective film continuously covers a surface of the assembly in the crystal separation region such that gaps are present between the columnar crystals. 3. The radiation detection material according to claim 1 or 2. (Configuration 4) In the aggregate, the columnar crystals are in contact with each other and connected to each other in the initial layer region, and voids are formed between the columnar crystals, the protective film is discontinuously formed on the columnar crystals in the voids; 4. The radiation detecting material according to any one of configurations 1 to 3. (Configuration 5) the protective film has a thickness in the initial layer region that is smaller than a thickness in the crystal separation region; 5. The radiation detecting material according to any one of configurations 1 to 4. (Configuration 6) The protective film has 16 to 25 molecular layers in the crystal separation region. 6. The radiation detecting material according to any one of configurations 1 to 5. (Configuration 7) The protective film has 25 molecular layers or less in the initial layer region. 7. The radiation detecting material according to any one of configurations 1 to 6. (Configuration 8) The protective film has a thickness of 4 nm to 5 nm in the crystal separation region. 8. The radiation detecting material according to any one of configurations 1 to 7. (Configuration 9) The protective film has a thickness of 5 nm or less in the initial layer region. 9. The radiation detecting material according to any one of configurations 1 to 8. (Configuration 10) The protective film comprises silica. 10. A radiation detecting material according to any one of configurations 1 to 9. (Configuration 11) The protective film is formed by converting a polysilazane-based inorganic polymer into silica. 11. The radiation detection material according to claim 10. (Configuration 12) A plurality of pixels each having a photoelectric conversion element; A radiation detection material according to any one of configurations 1 to 11, A radiation detector comprising: (Configuration 13) a radiation generating device that irradiates a subject with radiation; A radiography device having the radiation detector of configuration 12; a processor that performs arithmetic processing based on image information acquired by the radiation imaging apparatus; A radiological diagnostic system comprising: (Method 1) forming a phosphor having an aggregate of columnar crystals; forming a protective film that continuously covers the entire crystal separation region of the phosphor and partially covers the initial layer region of the phosphor; 1. A method for forming a radiation detecting material comprising: (Method 2) the protective film is formed so as to continuously cover the surface of the assembly in the crystal separation region such that gaps are present between the columnar crystals. A method for forming a radiation detection material according to method 1. (Method 3) In the aggregate, the columnar crystals are in contact with each other and connected to each other in the initial layer region, and voids are formed between the columnar crystals, the protective film is discontinuously formed on the columnar crystals in the voids; A method for forming a radiation detection material according to method 1 or 2. (Method 4) The protective film is formed by coating the phosphor with a liquid raw material. A method for forming a radiation detection material according to any one of Methods 1 to 3. (Method 5) The protective film is formed using the liquid raw material of silica. Method 5. A method for forming a radiation detection material according to method 4. (Method 6) The protective film is formed by applying the liquid raw material containing a silica conversion material at a concentration of 0.5% to 2% to the phosphor, impregnating the phosphor with the liquid raw material, and drying the liquid raw material. A method for forming a radiation detection material according to method 5. (Method 7) The liquid raw material is applied to the phosphor by scanning a nozzle of a spray coater. Method 7. A method for forming a radiation detection material according to method 6. (Method 8) The nozzle is scanned to apply the liquid raw material onto the phosphor so that the wet film thickness is 75 μm or more and 300 μm or less. Method 9. The method of forming a radiation detection material according to method 8. [Explanation of symbols]
[0062] 100: Substrate; 101: Columnar crystal; 102: Initial layer 103...Crystal separation region 104...Protective film 110...Columnar crystal group 111...void
Claims
1. A phosphor having an aggregate of columnar crystals; A protective film formed on the phosphor; Equipped with The protective film continuously covers the entire crystal separation region of the phosphor, and partially covers the initial layer region of the phosphor. A radiation detection material comprising:
2. The thickness of the protective film is equal to or less than the distance between the opposing columnar crystals. The radiation detection material of claim 1 .
3. the protective film continuously covers a surface of the assembly in the crystal separation region such that gaps are present between the columnar crystals. The radiation detection material of claim 1 .
4. In the aggregate, the columnar crystals are in contact with each other and connected to each other in the initial layer region, and voids are formed between the columnar crystals, the protective film is discontinuously formed on the columnar crystals in the voids; The radiation detection material of claim 1 .
5. the protective film has a thickness in the initial layer region that is smaller than a thickness in the crystal separation region; The radiation detection material of claim 1 .
6. The protective film has 16 to 25 molecular layers in the crystal separation region. The radiation detection material of claim 1 .
7. The protective film has a number of molecular layers of 25 or less in the initial layer region. The radiation detection material of claim 1 .
8. The protective film has a thickness of 4 nm to 5 nm in the crystal separation region. The radiation detection material of claim 1 .
9. The protective film has a thickness of 5 nm or less in the initial layer region. The radiation detection material of claim 1 .
10. The protective film comprises silica. The radiation detection material of claim 1 .
11. The protective film is formed by converting a polysilazane-based inorganic polymer into silica. The radiation detection material of claim 10.
12. A plurality of pixels each having a photoelectric conversion element; A radiation detection material according to any one of claims 1 to 11, A radiation detector comprising:
13. a radiation generating device that irradiates a subject with radiation; A radiography device having the radiation detector of claim 12; a processor that performs arithmetic processing based on image information acquired by the radiation imaging apparatus; A radiological diagnostic system comprising:
14. forming a phosphor having an aggregate of columnar crystals; forming a protective film that continuously covers the entire crystal separation region of the phosphor and partially covers the initial layer region of the phosphor; 1. A method for forming a radiation detecting material comprising:
15. the protective film is formed so as to continuously cover the surface of the assembly in the crystal separation region such that gaps are present between the columnar crystals. A method of forming the radiation detection material of claim 14.
16. In the aggregate, the columnar crystals are in contact with each other and connected to each other in the initial layer region, and voids are formed between the columnar crystals, the protective film is discontinuously formed on the columnar crystals in the voids; A method of forming the radiation detection material of claim 14.
17. The protective film is formed by coating the phosphor with a liquid raw material. A method of forming the radiation detection material of claim 14.
18. The protective film is formed using the liquid raw material of silica.
20. A method of forming the radiation detection material of claim 17.
19. The protective film is formed by applying the liquid source containing a silica conversion material at a concentration of 0.5% to 2% to the phosphor, impregnating the phosphor with the liquid source, and drying the liquid source.
20. A method of forming the radiation detection material of claim 18.
20. The liquid raw material is applied to the phosphor by scanning a nozzle of a spray coater.
20. A method of forming the radiation detection material of claim 17.
21. The nozzle is scanned to apply the liquid raw material onto the phosphor so that the wet film thickness is 75 μm or more and 300 μm or less.
21. A method of forming the radiation detection material of claim 20.
Citation Information
Patent Citations
Radiation detection apparatus and radiation detection system
JP2015141190A
Scintillator plate, radiation detector, and radiation detection system
JP2020041820A